Structural Characterization of Withanolide Glycosides from the Roots of Withania somnifera and Their Potential Biological Activities - Ji Won Ha; Jae Sik Yu; Bum Soo Lee; Dong-Min Kang; Mi-Jeong Ahn; Jung Kyu Kim; Ki Hyun Kim (Plants, 2022)
Withania somnifera (Solanaceae), commonly known as “ashwagandha”, is an ayurvedic medicinal plant that has been used for promoting good health and longevity. As part of our ongoing natural product research for the discovery of bioactive phytochemicals with novel structures, we conducted a phytochemical analysis of W. somnifera root, commonly used as an herbal medicine part. The phytochemical investigation aided by liquid chromatography-mass spectrometry (LC/MS)-based analysis led to the isolation of four withanolide glycosides (1–4), including one new compound, withanoside XII (1), from the methanol (MeOH) extract of W. somnifera root. The structure of the new compound was determined by nuclear magnetic resonance (NMR) spectroscopic data, high-resolution (HR) electrospray ionization (ESI) mass spectroscopy (MS), and electronic circular dichroism (ECD) data as well as enzymatic hydrolysis followed by LC/MS analysis. In addition, enzymatic hydrolysis of 1 afforded an aglycone (1a) of 1, which was identified as a new compound, withanoside XIIa (1a), by the interpretation of NMR spectroscopic data, HR-ESIMS, and ECD data. To the best of our knowledge, the structure of compound 2 (withagenin A diglucoside) was previously proposed by HRMS and MS/MS spectral data, without NMR experiment, and the physical and spectroscopic data of withagenin A diglucoside (2) are reported in this study for the first time. All the isolated compounds were evaluated for their anti-Helicobacter pylori, anti-oxidant, and anti-inflammatory activities. In the anti-Helicobacter pylori activity assay, compound 2 showed weak anti-H. pylori activity with 7.8% inhibition. All the isolated compounds showed significant ABTS radical scavenging activity. However, all isolates failed to show inhibitory activity against nitric oxide (NO) production in lipopolysaccharide-stimulated RAW 264.7 macrophage cells. This study demonstrated the experimental support that the W. somnifera root is rich in withanolides, and it can be a valuable natural resource for bioactive withanolides.